O lúdico na atitude interdisciplinar - Vilches, Manolo Perez (2009)
This research intends to show that the playful element is a relevant piece into the interdisciplinary process as an attitude .Although the Playful or Ludic terms have been exhaustive related to the questions about children´s cognitive formation for many autors, their dimension surpasse the limits of the school and childhood; the enchantment in the discovery of the world can be lived deeply by all and in any age and is closely related to the contact with the new, the challenger, the beauty and the fantastic. This work looks for not only to stand out the importance of the playful element in the school as in the daily routine of all people. The possibility of an interdisciplinary experience, while easing experiences that do not break up knowledge, gains important elements when playful manifests itself in simple things such as the architecture of the cities, the simplicity of toys, the beauty of arts, the magic of the numbers, or the delights of the gastronomy, among others situations. The satisfaction in knowing the strange, intuiting its secrets, in trying to dominate it and understanding it, in revisiting it, makes man a perpetual apprentice, from childhood to the maturity. When we dive in the satisfaction of the ludic experience there are no borders between knowledge and, when valuing the revelations that the disciplinarity knowing offers to us in each moment, we perceive the necessity of a look that rescues us to a totality . From the practical experience, this work establishes ways for the valuation of Ludic element as a powerful motivator of satisfaction of knowing in an interdisciplinary perspective